Toward an Original Forestry - Struthers, Rolf (UnderCurrents: Journal of Critical Environmental Studies, 1991)
On a day in early spring, I was sitting on a small hummock eating lunch, enjoying the warmth of the spring sun and relieving my legs after a good, long walk in the Woods when it happened. It takes a while, it never happens right away but sometimes, after hours of walking, thinking, and feeling my way along the paths of the Woods, it can happen. The wall drops and conversation begins. I breathe in fresh spring air and I feel my blood go rushing through me in a flood of exhilaration. "LIVE, BREATHE, AWAKEN" the Woods say, "Let us begin again." The ground, the smell of fresh rotting leaves, the sound of the trickling water, the hum of the first bumblebee in the nearby leaves, the unhurried wariness of the wolf spider hunting in the leaf mold, the up-shooting lush green of the trilliums and other wood spring flowers–all these things create a rhythm. I feel the rhythm coursing through me; I feel like I too am being renewed. I leap up and caper around briefly, then stop. And the moment is gone. But it is not completely gone. Many times now I have re-called that moment, and I am there. I and the Woods are speaking, the Woods saying LIFE and I exclaiming yes! here, life dig, root, push, lift, spread! The rhythm of spring echoes in my ears and fills my nose with its vibrant odour.